2020
DOI: 10.3389/fped.2020.00411
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Febrile Children Admitted to the ICU Following an Unscheduled ED Revisit Within 72 h, a Case–Control Study

Abstract: The purpose of this article was to demonstrate related characteristics of intensive care unit (ICU) admission after an unscheduled revisit by febrile children visiting the emergency department (ED). Method: We performed a retrospective study in a tertiary medical center from 2010 to 2016. Patients whose chief complaint was fever and who were admitted to the ICU following a 72-h return visit to the ED were included, and we selected patients who were discharged from the same emergency department for comparison. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…We calculated the SI and SIPA values from medical records documented in the research database for the included patients at the time of ED arrival and 24 h after admission. These values were then categorized as either abnormal (i.e., above the normal SI range or normal SIPA value for age range) or normal based on the normal range of vital signs in different age groups that were adopted in recent studies ( 17 , 25 , 27 ). We also calculated delta SI by subtracting the SI value at 24 h after admission from the SI value at admission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated the SI and SIPA values from medical records documented in the research database for the included patients at the time of ED arrival and 24 h after admission. These values were then categorized as either abnormal (i.e., above the normal SI range or normal SIPA value for age range) or normal based on the normal range of vital signs in different age groups that were adopted in recent studies ( 17 , 25 , 27 ). We also calculated delta SI by subtracting the SI value at 24 h after admission from the SI value at admission.…”
Section: Methodsmentioning
confidence: 99%
“…There is a paucity of data on this subject in non-traumatic pediatric patients. One study conducted in 2020 indicated that febrile children with elevated SIPA values on the initial emergency department (ED) visit were associated with ICU admission following an unscheduled ED revisit within 72 h ( 27 ). Considering that the conclusions of most studies on SIPA were confined to trauma patients, this study attempted to expand the use of this tool to include additional pediatric populations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have sought to identify the risk factors for return ED visits in the general ED population [13][14][15][16][17]. Recently, several revisit prediction models have been developed for children and elderly patients with specific Healthcare 2021, 9, 1470 2 of 10 diseases, such as urinary tract infection and asthma [18][19][20][21][22][23]. It is imperative for emergency physicians to identify the risk of revisiting before discharge among patients presenting with NSAP, one of the most common complaints associated with return visits.…”
Section: Introductionmentioning
confidence: 99%
“…Return visits to the ED are stressful for the physician and constitute a worldwide phenomenon that may be partially preventable. Studies have described short-term revisit after hospital discharge exploring predicting factors, 2,3,5,10 but only a few studies have investigated which factors could be useful in predicting outcomes of a second visit 11,12 . In this cohort of children attending a PED with high levels of CRP (≥150 mg/L) at the initial visit, the level of CRP was not useful in predicting clinical outcomes of children who returned for a second visit within 7 days.…”
Section: Discussionmentioning
confidence: 85%